<u>ANSWER: </u>
The area of the triangle bounded by the y-axis is ![\frac{7938}{4225} \sqrt{65} \text { unit }^{2}](https://tex.z-dn.net/?f=%5Cfrac%7B7938%7D%7B4225%7D%20%5Csqrt%7B65%7D%20%5Ctext%20%7B%20unit%20%7D%5E%7B2%7D)
<u>SOLUTION:</u>
Given, ![f(x)=9-\frac{-4}{7} x](https://tex.z-dn.net/?f=f%28x%29%3D9-%5Cfrac%7B-4%7D%7B7%7D%20x)
Consider f(x) = y. Hence we get
--- eqn 1
![y=9-\frac{4}{7} x](https://tex.z-dn.net/?f=y%3D9-%5Cfrac%7B4%7D%7B7%7D%20x)
On rewriting the terms we get
4x + 7y – 63 = 0
As the triangle is bounded by two perpendicular lines, it is an right angle triangle with y-axis as hypotenuse.
Area of right angle triangle =
where a, b are lengths of sides other than hypotenuse.
So, we need find length of f(x) and its perpendicular line.
First let us find perpendicular line equation.
Slope of f(x) = ![\frac{-x \text { coefficient }}{y \text { coefficient }}=\frac{-4}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-x%20%5Ctext%20%7B%20coefficient%20%7D%7D%7By%20%5Ctext%20%7B%20coefficient%20%7D%7D%3D%5Cfrac%7B-4%7D%7B7%7D)
So, slope of perpendicular line = ![\frac{-1}{\text {slope of } f(x)}=\frac{7}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%7D%7B%5Ctext%20%7Bslope%20of%20%7D%20f%28x%29%7D%3D%5Cfrac%7B7%7D%7B4%7D)
Perpendicular line is passing through origin(0,0).So by using point slope formula,
![y-y_{1}=m\left(x-x_{1}\right)](https://tex.z-dn.net/?f=y-y_%7B1%7D%3Dm%5Cleft%28x-x_%7B1%7D%5Cright%29)
Where m is the slope and ![\left(\mathrm{x}_{1}, \mathrm{y}_{1}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cmathrm%7Bx%7D_%7B1%7D%2C%20%5Cmathrm%7By%7D_%7B1%7D%5Cright%29)
![y-0=\frac{7}{4}(x-0)](https://tex.z-dn.net/?f=y-0%3D%5Cfrac%7B7%7D%7B4%7D%28x-0%29)
--- eqn 2
4y = 7x
7x – 4y = 0
now, let us find the vertices of triangle, one of them is origin,
second one is point of intersection of y-axis and f(x)
for points on y-axis x will be zero, to get y value, put x =0 int f(x)
0 + 7y – 63 = 0
7y = 63
y = 9
Hence, the point of intersection is (0, 9)
Third vertex is point of intersection of f(x) and its perpendicular line.
So, solve (1) and (2)
![\begin{array}{l}{9-\frac{4}{7} x=\frac{7}{4} x} \\\\ {9 \times 4-\frac{4 \times 4}{7} x=7 x} \\\\ {36 \times 7-16 x=7 \times 7 x} \\\\ {252-16 x=49 x} \\\\ {49 x+16 x=252} \\\\ {65 x=252} \\\\ {x=\frac{252}{65}}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B9-%5Cfrac%7B4%7D%7B7%7D%20x%3D%5Cfrac%7B7%7D%7B4%7D%20x%7D%20%5C%5C%5C%5C%20%7B9%20%5Ctimes%204-%5Cfrac%7B4%20%5Ctimes%204%7D%7B7%7D%20x%3D7%20x%7D%20%5C%5C%5C%5C%20%7B36%20%5Ctimes%207-16%20x%3D7%20%5Ctimes%207%20x%7D%20%5C%5C%5C%5C%20%7B252-16%20x%3D49%20x%7D%20%5C%5C%5C%5C%20%7B49%20x%2B16%20x%3D252%7D%20%5C%5C%5C%5C%20%7B65%20x%3D252%7D%20%5C%5C%5C%5C%20%7Bx%3D%5Cfrac%7B252%7D%7B65%7D%7D%5Cend%7Barray%7D)
Put x value in (2)
![\begin{array}{l}{y=\frac{7}{4} \times \frac{252}{65}} \\\\ {y=\frac{441}{65}}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7By%3D%5Cfrac%7B7%7D%7B4%7D%20%5Ctimes%20%5Cfrac%7B252%7D%7B65%7D%7D%20%5C%5C%5C%5C%20%7By%3D%5Cfrac%7B441%7D%7B65%7D%7D%5Cend%7Barray%7D)
So, the point of intersection is ![\left(\frac{252}{65}, \frac{441}{65}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cfrac%7B252%7D%7B65%7D%2C%20%5Cfrac%7B441%7D%7B65%7D%5Cright%29)
Length of f(x) is distance between
and (0,9)
![\begin{aligned} \text { Length } &=\sqrt{\left(0-\frac{252}{65}\right)^{2}+\left(9-\frac{441}{65}\right)^{2}} \\ &=\sqrt{\left(\frac{252}{65}\right)^{2}+0} \\ &=\frac{252}{65} \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%5Ctext%20%7B%20Length%20%7D%20%26%3D%5Csqrt%7B%5Cleft%280-%5Cfrac%7B252%7D%7B65%7D%5Cright%29%5E%7B2%7D%2B%5Cleft%289-%5Cfrac%7B441%7D%7B65%7D%5Cright%29%5E%7B2%7D%7D%20%5C%5C%20%26%3D%5Csqrt%7B%5Cleft%28%5Cfrac%7B252%7D%7B65%7D%5Cright%29%5E%7B2%7D%2B0%7D%20%5C%5C%20%26%3D%5Cfrac%7B252%7D%7B65%7D%20%5Cend%7Baligned%7D)
Now, length of perpendicular of f(x) is distance between ![\left(\frac{252}{65}, \frac{441}{65}\right) \text { and }(0,0)](https://tex.z-dn.net/?f=%5Cleft%28%5Cfrac%7B252%7D%7B65%7D%2C%20%5Cfrac%7B441%7D%7B65%7D%5Cright%29%20%5Ctext%20%7B%20and%20%7D%280%2C0%29)
![\begin{aligned} \text { Length } &=\sqrt{\left(0-\frac{252}{65}\right)^{2}+\left(0-\frac{441}{65}\right)^{2}} \\ &=\sqrt{\left(\frac{252}{65}\right)^{2}+\left(\frac{441}{65}\right)^{2}} \\ &=\frac{\sqrt{(12 \times 21)^{2}+(21 \times 21)^{2}}}{65} \\ &=\frac{63}{65} \sqrt{65} \end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%5Ctext%20%7B%20Length%20%7D%20%26%3D%5Csqrt%7B%5Cleft%280-%5Cfrac%7B252%7D%7B65%7D%5Cright%29%5E%7B2%7D%2B%5Cleft%280-%5Cfrac%7B441%7D%7B65%7D%5Cright%29%5E%7B2%7D%7D%20%5C%5C%20%26%3D%5Csqrt%7B%5Cleft%28%5Cfrac%7B252%7D%7B65%7D%5Cright%29%5E%7B2%7D%2B%5Cleft%28%5Cfrac%7B441%7D%7B65%7D%5Cright%29%5E%7B2%7D%7D%20%5C%5C%20%26%3D%5Cfrac%7B%5Csqrt%7B%2812%20%5Ctimes%2021%29%5E%7B2%7D%2B%2821%20%5Ctimes%2021%29%5E%7B2%7D%7D%7D%7B65%7D%20%5C%5C%20%26%3D%5Cfrac%7B63%7D%7B65%7D%20%5Csqrt%7B65%7D%20%5Cend%7Baligned%7D)
Now, area of right angle triangle = ![\frac{1}{2} \times \frac{252}{65} \times \frac{63}{65} \sqrt{65}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%5Ctimes%20%5Cfrac%7B252%7D%7B65%7D%20%5Ctimes%20%5Cfrac%7B63%7D%7B65%7D%20%5Csqrt%7B65%7D)
![=\frac{7938}{4225} \sqrt{65} \text { unit }^{2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B7938%7D%7B4225%7D%20%5Csqrt%7B65%7D%20%5Ctext%20%7B%20unit%20%7D%5E%7B2%7D)
Hence, the area of the triangle is ![\frac{7938}{4225} \sqrt{65} \text { unit }^{2}](https://tex.z-dn.net/?f=%5Cfrac%7B7938%7D%7B4225%7D%20%5Csqrt%7B65%7D%20%5Ctext%20%7B%20unit%20%7D%5E%7B2%7D)